2011
DOI: 10.1080/19440049.2011.589036
|View full text |Cite
|
Sign up to set email alerts
|

Migration of bisphenol A from polycarbonate baby bottles purchased in the Spanish market by liquid chromatography and fluorescence detection

Abstract: During the last decade the safety of bisphenol A (BPA) monomer in polycarbonate baby bottles has drawn the attention of both the public and the scientific community. This paper presents the results of BPA migration from polycarbonate baby bottles bought in the Spanish market, into simulant B (3% acetic acid), 50% ethanol and into real food (reconstituted infant formula). Furthermore, it was also the objective of this study to assess the suitability of 50% ethanol as a simulant for infant formula. BPA was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…It is important to note that the legal limit was 600 mg/kg polycarbonate bottles at the time of purchase, preceding the precautionary ban implemented from 1 June 2011 (EU 2011a(EU , 2011b. This confirms the results from a previous monitoring study carried out by the JRC in 2000 (Simoneau et al 2000) and from the most recent studies and enforcement campaigns (Food and Consumer Product Safety Authority 2008; Kubwabo et al 2009;Santillana et al 2011) that the likelihood of migration of BPA into the official simulant for milk (50% EtOH) is very low and remains at very minute amounts. Bottles were also analysed for other compounds, in work currently in progress, without showing any notable release .…”
Section: Bottles Made Of Polycarbonatesupporting
confidence: 93%
See 1 more Smart Citation
“…It is important to note that the legal limit was 600 mg/kg polycarbonate bottles at the time of purchase, preceding the precautionary ban implemented from 1 June 2011 (EU 2011a(EU , 2011b. This confirms the results from a previous monitoring study carried out by the JRC in 2000 (Simoneau et al 2000) and from the most recent studies and enforcement campaigns (Food and Consumer Product Safety Authority 2008; Kubwabo et al 2009;Santillana et al 2011) that the likelihood of migration of BPA into the official simulant for milk (50% EtOH) is very low and remains at very minute amounts. Bottles were also analysed for other compounds, in work currently in progress, without showing any notable release .…”
Section: Bottles Made Of Polycarbonatesupporting
confidence: 93%
“…Krishnan et al (1993) reported that BPA exhibited estrogenic activity. Since small amounts of BPA may leach from polycarbonate material into foodstuff, many studies have been conducted and reviewed on BPA release from baby bottles from mild to harsh conditions as well as ageing (Mountfort et al 1997;Brede et al 2003;BiedermannFood andConsumer Product Safety Authority 2005, 2008;Brem et al 2008;Ehlert et al 2008;Maragou et al 2008;Kubwabo et al 2009;Hoekstra and Simoneau 2011;Santillana et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Regarding BPA, many migration studies can be found in the literature during the last years. Of special interest are those performed from plastic baby bottles and baby bottle liners [69][70][71][72][73]. For instance, Kubwako et al [70] studied the migration of BPA into water (used as food simulant) from polycarbonate baby bottles, non-polycarbonate baby bottles, baby bottle liners and glass baby bottles.…”
Section: Food Packaging Migration Studiesmentioning
confidence: 99%
“…LC has also been used in combination with fluorescence detection (FLD) (Yi et al 2010;Santillana et al 2011) and diode array detection (DAD) (Rezaee et al 2009). However, these methods are characterised by poor selectivity and sensitivity, resulting in high LODs and LOQs.…”
Section: Introductionmentioning
confidence: 99%